Tumor infection with human herpes viruses and features of peripheral blood lymphocyte subset composition in patients with uveal melanoma - Elena V. Svetlova; N. V. Balatskaya; I. G. Kulikova; S. V. Saakyan; I. V. Svirina; A. E. Andryushin; E. B. Myakoshina (Инфекция и иммунитет)
Introduction. Currently, a role for human herpes viruses (HHV) in development of ocular oncopathology remains one of the poorly explored issues. An important factor contributing to neoplastic progression is impaired immunosurveillance particularly alterations in quantitative and qualitative composition of the hallmark peripheral blood lymphocyte subsets. The aim of the study was to determine and analyze peripheral blood lymphocyte subset composition in patients with uveal melanoma (UM) assessing human herpes viruses (HHV) infection in tumor material. Materials and methods. Biomaterial from 99 patients with uveal tract tumors was examined by real-time polymerase chain reaction (rt-PCR) for DNA presence coupled to herpes virus type 1 and 2 (HSV-1,2), Varicella Zoster virus (VZV), cytomegalovirus (CMV), Epstein–Barr virus (EBV), human herpes virus types 6 and 8 (HHV-6, HHV-8). A total of 231 test samples (tumor tissue (n = 99), blood (n = 132)) were examined. Commercial test-systems of “Vector-Best” (Russia) were used for rt-PCR staging. Peripheral blood lymphocyte subset composition in all patients was studied by laser cytofluorometry on “BD FACSCanto II” flow cytometer. The control group included 33 healthy donors. Statistical data processing was performed using “Biostatd”, “Excel” (t — Student’s t-test, level of statistical significance: p 0.05) software. Results. HHV DNA was detected in the tumor material from 11.3% of patients (n = 11): in 72.7% of cases EBV, in 18.2% — HHV-6. Co-infection with EBV and HHV-6 was detected in 1 case (retinal pigment epithelium adenocarcinoma). According to the PCR data, patients were divided into 2 groups based on tumor infectivity: Group 1 — HHV+ and Group 2 — HHV–. Patients from HHV+ group had significantly increased and decreased total T-cell (CD3+) and NK-cell count, respectively, compared with patients lacking HHV DNA in tumor tissue and control group. Individual analysis of frequencies deviating from normal range showed that HHV+ group had 3-fold more often increased percentage of CD3+ lymphocytes, 2-fold more often absolute count of CD3+CD4+CD8+ cells, 2.3-fold more often rise in CD4+/CD8+ ratio. Conclusion. The obtained data suggest that viruses may be involved in maintaining immunological resistance in tumor patients.